The hunt for the perfect biomarker in nasopharyngeal carcinoma—the RRAS “race” beyond Epstein-Barr virus? - Tan, Mark T. L.; Wee, Joseph T. S.; Chua, Melvin L. K. (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Nasopharyngeal carcinoma (NPC) is a distinct malignancy from other epithelial head and neck cancers, given its specific geographical and demographic distribution. It is endemic in parts of East and Southeastern Asia, and North and East Africa, and is more common in men than women (3:1 ratio) (1). The endemic variant of NPC is invariably associated with the Epstein-Barr virus (EBV).